Analisis Nilai Tambah Dan Kelayakan Finansial Kerupuk Kulit Ikan Tuna Sirip Kuning (Thunnus albacares) UD. Putra Susila - Simanjuntak, Yosefina PG.; Wiranatha, Anak Agung Putu Agung Suryawan; Suwariani , Ni Putu (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Yellowfin tuna fish skin crackers are the flagship product at UD. Putra Susila, and not many other companies produce it. This study aims to determine the added value of processing Yellowfin tuna fish skin crackers at UD. Putra Susila, and to undertake the financial feasibility of the production process of Yellowfin tuna fish skin crackers at UD. Putra Susila. The financial feasibility study used the calculation of profit and loss analysis, Net Present Value, Internal Rate of Return, Net B/C Ratio, Payback Period, and Break Event Point, and used the Hayami method to determine the added value. The Yellowfin tuna fish skin crackers business is feasible, i.e the Net Present Value of Rp. 712.280.532. Internal Rate of Return of 56,72%, Payback Period for 1 year 7 months, and Net B/C Ratio of 6,416. The results showed that the added value of Yellowfin tuna fish skin crackers was Rp. 37.400 per kg, a value-added income ratio of 77,92%. Sensitivity analysis showed that both 7%-9% increasing in operating costs and 7%-9% decreasing in revenue resulted in a positive NVP. Therefore, the Yellowfin tuna fish skin crackers business is feasible.